Religion and Politics in Francisco Bilbao - Garcés Marrero, Roberto (2023)
This text aims to analyze the link that the Chilean philosopher Francisco Bilbao established between religion and political life, as well as the implication that according to him it had for South America. For this, his theoretical bases, his vision of the geopolitics of the time and his concept of religion-freedom are reconstructed. Many of this author's ideas prefigure important discussions that have not yet ended.